Simulation and modeling methodologies, technologies and applications : International Conference, SIMULTECH 2015 Colmar, France, July 21-23, 2015, revised selected papers /: International Conference, SIMULTECH 2015 Colmar, France, July 21-23, 2015, revised selected papers. ([2016]) - Unknown
No abstract available